Manufacturing and categorization of AL/TIB2 metal matrix compound by means of stir casting method. (2021) - Kumar Singh, Pankaj; Kumar Singh, Pradeep; Sharma, Kamal
Abstract: In this study, the aluminum 7075 alloy was taken as matrix material & the titanium di-boride was taken as reinforcing material. The composite metal matrix has manufactured with the assistance of stir casting model with di-boride titanium reinforcing power along with alloy of aluminum and composites mechanical characteristics have been perceived. The powder called di-boride titanium of mesh magnitude 325 is accumulated in matric of alloy called aluminum, where samples were manufactured by utilizing stir casting model with 3, 9, 6, 12 ratio by percentage of weight. Here, specimens that are manufactured carried out tests like strength of impact, tensile strength, hardness where their values have been examined with alloy for assessing the composite mechanical properties.